It’s what I’m going to do! Possible feminisms in the film adaptation of Wonder Woman - Do Carmo Dalbeto, Lucas [UNESP]; Carlos Marques, José [UNESP] (My University, 2020)
Supported by feminist theory of cinema and Foucault's perspective of discourse, this article presents a reading of the possible feminist manifestations of Wonder Woman (2017). It is premised on the statement of Zoe Williams, who understands it as a feminist act. As re-sult, it is believed that the film promotes a small break in the hegemony of these pro-ductions, but it is still inscribed in the logic of consumption.
¡Eso es lo que haré! Posibles feminismos en la adaptación cinematográfica de Mujer Maravilla
É o que eu vou fazer! Feminismos possíveis na adaptação cinematográfica de Mulher Maravilha
Keywords: feminist critical theory of cinema; feminist discourse; superheroine; Wonder Woman